BAHASA PENDIDIKAN INDONESIA DAN AKAR POLITIK PENDIDIKAN NASIONAL PRA-KEMERDEKAAN - Muhamad Asngad Rudisunhaji (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
The cultural fight towards the cultural manipulation conducted by the Dutch agressor shows an education aspect to Indonesian in general. Such cultural fight delivers a political stream as an antithesis action to the agressor’s political policy in education. One important decision which shows this fight is when Malay language was anonimously decided to be the national identity of Indonesian and was confirmed to be the formal language of the nation. In this article, Malay language and Bahasa Indonesia are not confronted, but are used in accordance to its appropriate context.